Morocco : 2007 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that macroeconomic conditions of Morocco remain strong. Average growth has reached 5.4 percent per year since 2001, 3.4 percentage points higher than in the 1990s, reflecting the ongoing diversification of the nonagricultural sector and its increased resilience to shocks. As a result, real per-capita income is on the rise and the unemployment rate has started to decline. The current account is expected to record its seventh consecutive surplus in 2007, thanks to strong remittances and tourism receipts. The public finance situation has also strengthened.